Предмет: Алгебра,
автор: gsf22
РЕШИТЕ НЕРАВЕНСТВО,ПРОШУУУ
( х-3)2>х(х-6)
Ответы
Автор ответа:
1
Перемножим
2x-6>x^2-6x
переносим в левую часть все
2x-6-x^2+6x>0
-x^2+8x-6>0
D=64 -4*(-1)*(-6)
D=40
X1=-8+√40/-2
X2=-8-√40/-2
2x-6>x^2-6x
переносим в левую часть все
2x-6-x^2+6x>0
-x^2+8x-6>0
D=64 -4*(-1)*(-6)
D=40
X1=-8+√40/-2
X2=-8-√40/-2
Приложения:
![](https://files.topotvet.com/i/5dc/5dc6a2e6a85648db6d43854456813ac4.jpg)
Похожие вопросы
Предмет: Английский язык,
автор: ilyaton
Предмет: Физика,
автор: Ktototamxd
Предмет: Физика,
автор: tepacaw477
Предмет: Математика,
автор: колян2009
Предмет: Алгебра,
автор: LampovayaNyashka